PRIVATE BRITISH SCHOOLS IN BUENOS AIRES 1820-1884 (2013)
Education in Buenos Aires was an ignored subject by histotians in Argentina even before Common Education Law 1884. This article aims to investigate education world in Buenos Aires by studying private schools held by English, Scotches, Irish, and Americans and therefore their decendants that settled in the city since 1820.  For this investigation we worked with forgein schools press advertisement for English speakers, police records, and National oficial registration Document for schools in 1872 and English speakers experts opinion on children and education of foreing people’ children, because of these sources study we found that English private schools were part of a diversified Educational world in Buenos Aires, in order to develop a privileged spot for native and foreigners education. These schools offered a variety of subjects being more  complex than public schools’ and other similar private schools offer  getting to educate several important members of local society, presenting itself as a new alternative to the poor and ineficient State’s educational system during 19th century.